CAP AND FRAUD. - FUNK, MCKENZIE (Foreign Policy)
The article looks at a trend of computer hackers stealing and reselling carbon credits and the impact on the European Union (EU) emissions trading, or cap-and-trade, program designed to lower greenhouse gas emissions as part of a policy to limit climate change. It profiles British hackers Matthew Beddoes and Jasdeep Singh Randhawa and discusses the efforts of law enforcement agencies including the International Criminal Police Organization (Interpol) to address the problem. Topics include existing or planned cap-and-trade systems outside of Europe, various types of fraud that have damaged the European emissions trading system, and assessments of the potential of emissions trading as a climate change mitigation strategy.